Menyingkap Kabut Tebal Kedaulatan - Sutoro Eko Yunanto; Guno Tri Tjahjoko (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2020)
Government Science has not become a scientific discipline and has not become a perspective in reading phenomena in society with government theories. Where the basic function of government science is to enlighten the government, it must criticize the government, not to insult and deny it, but instead have the aim to glorify, prioritize and strengthen the government. To return the science of government to the ultimate goal of a sovereign people, it is necessary to critically review it from the perspective of decolonization, reconstitution and repolitization.